The effects of alcohol hangover on future drinking behavior and the development of alcohol problems. (March 2018) - Courtney, Kelly E.; Worley, Matthew; Castro, Norma; Tapert, Susan F.
Abstract: Introduction: Alcohol hangover experiences in young adulthood have been shown to predict more subsequent alcohol problems. Hangover susceptibility appears to be partially heritable and related to family history of alcohol use disorders. However, very little is known about the developmental course of these associations and whether they are accounted for by an individual's drinking history. The goal of this study is to investigate the prospective and unique relationships between family history of alcohol use disorders, severity of alcohol hangover experiences in adolescence, and later alcohol use and related problems measured over 13 years. Methods: Participants were first assessed on family history at age 12–14, prior to initiating drinking, and re-assessed annually on hangover severity, drinks per drinking day (DPDD), and alcohol-related problems throughout the 13-year follow-up period ( n  = 205; 59% male). Results: In mixed effects negative binomial regression models, greater family history density scores predicted more future DPDD (Incidence Rate Ratio [IRR] = 1.19, p  = 0.04), alcohol problems (IRR = 1.64, p  = 0.05), and future hangover severity (IRR = 1.24; p  = 0.01). In turn, greater hangover severity predicted more future DPDD (IRR = 1.03; p  = 0.002) and alcohol problems (IRR = 1.12, p  < 0.001), and hangover severity mediated the relationship between family history and alcohol use/problems. All models controlled for participant age, sex, and past drinking behavior (where relevant). Conclusions: These results advance the alcohol hangover experience during late adolescence as a clinically relevant and uniquely informative marker of future alcohol use and problems, above and beyond that of prior personal or familial drinking history. Highlights: Hangover severity in adolescence predicts greater future alcohol use and problems. Hangover severity mediates the path between family history and alcohol outcomes. Hangovers are a clinically relevant marker of future alcohol outcomes.